Relative spore and pollen abundances from open-cast lignite mine Helmstedt - Walter Riegel; Olaf K Lenz; Volker Wilde (PANGAEA, 2017)
Tropical climates reached their northernmost expansion during the early Paleogene greenhouse phase, supporting a paratropical biota as far north as the southern shore of the ancient North Sea. There, relative sea-level fluctuations led to the formation of transgressive-regressive sequences, exposed in open-cast lignite mines in the area of Helmstedt (Lower Saxony, Germany), which record environmental changes at the marine-terrestrial interface. We studied an example from the middle Eocene of the Helmstedt Mine from which we reconstruct ecological successions from open estuary to meandering river environments, which represent vegetation at the Paleogene climatic optimum. In the absence of vertebrate and shelly fossils, environmental interpretations are made exclusively on plant matter in the sediment. Vegetational reconstructions are based mainly on quantitative palynological analyses, supported by paleobotanical and organic-petrographical evidence and confirmed by Principal Component Analysis. Diverse dinocyst assemblages in conjunction with Ophiomorpha-type bioturbation indicate open estuarine conditions. These are succeeded by mangrove, represented by pollen of Rhizophora, Avicennia, Nypa and the form species Psilodiporites iszkaszentgoergyi, and marsh environments, indicated by pollen of Restionaceae, Sparganiaceae/Typhaceae and fern spores. Subsequent lowland mire forests are characterized by a dominance of either the Tricolporopollenites cingulum group (Fagaceae) or triporate pollen of the Triporopollenites robustus/rhenanus complex (Myricaceae/Betulaceae). Within this landscape coexists a meandering river system, represented by channel lag and point-bar deposits of the active channel and by the clastic to lignitic sedimentary fill of an abandoned channel.
Supplement to: Riegel, W et al. (2015): From open estuary to meandering river in a greenhouse world: an ecological case study from the middle Eocene of Helmstedt, Northern Germany. Palaios, 30(4), 304-326, https://doi.org/10.2110/palo.2014.005